Reduction and Oxidation of Cu Species in Cu-Faujasites Studied by IR Spectroscopy - Łukasz Kuterasiński; Jerzy Podobiński; Ewa Madej; Małgorzata Smoliło-Utrata; Dorota Rutkowska-Zbik; Jerzy Datka (Molecules, 2020)
The process of reduction (by hydrogen and ethanol) and oxidation (by oxygen and NO) of Cu sites in dealuminated faujasite-type zeolites (of Si/Al = 31) was studied by infrared (IR) spectroscopy with CO (for Cu+) and NO (for Cu2+) as probe molecules. Two zeolites were studied: one of them contained mostly Cu+exch., whereas another one contained mostly Cu2+ and Cu+ox. The susceptibility of various forms of Cu for reduction were investigated. IR experiments of CO sorption evidenced that Cu+ox. was more prone for the reduction than Cu+exch. According to NO sorption studies, Cu2+exch. was reduced in the first order before Cu2+ox. Ethanol reduced mostly Cu2+ and, also, some amounts of Cu+. The treatment with oxygen caused the oxidation of Cu+ (both Cu+exch. and Cu+ox.) to Cu2+. The adsorption of NO at 190K produced Cu+(NO)2 dinitrosyls, but heating to room temperature transformed dinitrosyls to mononitrosyls and increased the Cu2+ content.